Sociocultural Based Language Learning for Strengthening Communicative Competence - Anna Gabrielyan; Yana Levchenko; Anita Soejianto (Journal of Language Studies, 2026)
This study explores the role of sociocultural-based language learning in strengthening communicative competence among language learners. Grounded in sociocultural theory, the research emphasizes the importance of social interaction, cultural context, and meaningful communication in language acquisition. A qualitative descriptive approach was employed, involving observations and interviews with students and teachers in a secondary education setting. The findings reveal that integrating sociocultural elements, such as authentic materials, collaborative activities, and real-life communication practices, significantly enhances learners’ communicative abilities. Furthermore, the study highlights that learners develop not only linguistic skills but also sociolinguistic and intercultural competencies. These findings are consistent with previous studies emphasizing the mediating role of social interaction in language learning. The study concludes that sociocultural-based instruction provides a holistic framework for developing communicative competence and recommends its integration into language curricula.